The Efficacy of Inclusive Education Practices in Zimbabwean Rural Schools: Challenges and Opportunities - Omega Mangena; Nowell Chidakwa (Educational Challenges)
Purpose. The purpose of this research is to assess the extent of implementation and the efficiency of inclusive education practices at a selected secondary school in Zimbabwe.